Geochemistry and zircon U-Pb geochronology of the Dak Krong plutonic rocks in the Kontum Massif (central Vietnam) and their petrogenetic implications - Nguyen Kim, Hoang; Nong Thi Quynh, Anh; Pham, Minh; Pham Trung, Hieu; Nguyen Thanh, Thao (Vietnam Journal of Earth Sciences, 2023)
Dak Krong plutonic rocks are found in the Kontum Massif along the N-S-oriented Po Ko River and mainly within the distributive area of the Ben Giang-Que Son granitic bodies. The Hai Van complex crosscuts the Dak-Krong rocks. They are predominantly composed of plagioclase (35-47%), quartz (29-30%), K-feldspar (20-28%), and minor biotite (3-4%). Geochemically, they are characterized by meta- to peraluminous and high-K affinities and straddle I- and S-type granite fields. Zircon U-Pb dating results yielded two main magmatic stages (ca. 258 Ma and ca. 245 Ma) spanning two phases of magmatism presumably accepted as being associated with the Paleo-Tethys Ocean evolution: latest subduction to syn-collisional phases. The Hf isotope data from zircon with eHf(t) ranging between -6.4 and -0.5 indicates a crustal signature. From the results of eHf(t) values along with zircon Hf model ages (TDM2) ranging from 1165-1497 Ma, it is presumable that the Dak Krong plutonic rocks are the product of the partial melting of Mesoproterozoic crustal materials with a negligible contribution of mantle materials. Together with other Permian-Triassic magmatic complexes throughout the Kontum Massif (e.g., Ben Giang-Que Son, Hai Van, and Van Canh complexes) and other plutonic further to the north along the Truong Son Belt and the Song Ma suture zone, the Dak Krong plutonic rocks represent magmatism generated by the amalgamation of Indochina and South China during the Late Permian-Early Triassic, referred to as Indosinian orogeny.